2016
DOI: 10.1590/abd1806-4841.20164682
|View full text |Cite
|
Sign up to set email alerts
|

Squamoid eccrine ductal carcinoma

Abstract: Squamoid eccrine ductal carcinoma is an eccrine carcinoma subtype, and only twelve cases have been reported until now. It is a rare tumor and its histopathological diagnosis is difficult. Almost half of patients are misdiagnosed as squamous cell carcinoma by the incisional biopsy. We report the thirteenth case of squamoid eccrine ductal carcinoma. Female patient, 72 years old, in the last 6 months presenting erythematous, keratotic and ulcerated papules on the nose. The incisional biopsy diagnosed squamoid ecc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…White individuals have a higher risk than black. The most significant analysis is 30 patients subsumed into a publication [ 160 ].…”
Section: Tumors With Apocrine and Eccrine Differentiationmentioning
confidence: 99%
See 2 more Smart Citations
“…White individuals have a higher risk than black. The most significant analysis is 30 patients subsumed into a publication [ 160 ].…”
Section: Tumors With Apocrine and Eccrine Differentiationmentioning
confidence: 99%
“…In the macroscopic and microscopic evaluation, the cytologic atypia was moderate to severe, ulceration (47%), necrosis (23%), and perineural and lymphovascular infiltration (27% and 6%, respectively). Distant metastasis is relatively rare [ 160 ].…”
Section: Tumors With Apocrine and Eccrine Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Over the course of almost 20 years, less than a dozen subsequent cases of this entity were reported, many in the form of case reports or small case series. 9,10 In 2016, a clinicopathologic study of 30 cases was published and showed that SEDC typically manifests as ulcerated nodules and plaques in sun-exposed areas, primarily the face, in the seventh and eighth decades of life. Histologically, these tumors demonstrate a biphasic appearance.…”
mentioning
confidence: 99%
“…This clinical non-specificity often leads to incomplete biopsies (shavings), diagnostic delay, and negative impact on prognosis. 2 , 3 …”
mentioning
confidence: 99%